Kesetaraan hula-hula dengan boru dalam budaya Batak Toba: Tinjauan sosio-teologis Galatia 3:28 - Simanjuntak, Roy Martin; Prananingtyas, Niken Dewi; Patora, Marianus; Soegijono, Harry; Nugroho, Setya Hadi (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2021)
Dalihan Na Tolu is a culture and philosophy of life of the Batak people. It is not only the kinship relationship contained in it but also as a driving force for the life order of the believers. In the Dalihan Na Tolu philosophy, there is a relationship that needs to be evaluated in relation to social equality, namely the relationship between Hula-hula and Boru. The perspective of Christian faith will complement the philosophy of Dalihan Na Tolu if it is built in the love and sacrifice of Christ, which is ultimately driven by love in the Dalihan Na Tolu philosophy. This study used a qualitative literature approach, which uses descriptive methods, and analysis-argumentative. descriptive, analysis-interpretive, and argumentation-comparative. With the constructive comparative aid method, this study uses various literature sources, such as books, journal articles, and dissemination on web pages to gain new insights from the text being studied. The conclusion that can be drawn is that the theology of social equality in the perspective of the Christian faith should complement the philosophy of Dalihan Na Tolu which centers on the love and sacrifice of Christ. The relationship between hula-hula and boru is no longer seen as an order of law that implies a curse but rather as local wisdom that enriches mission values to introduce the love of Christ through the Dalihan Na Tolu philosophy. AbstrakDalihan Na Tolu adalah sebuah budaya dan falsafah hidup bagi orang Batak. Tidak hanya hubungan kekerabatan yang terkandung di dalamnya, te-tapi juga sebagai penggerak tatanan kehidupan. Dalam falsafah Dalihan Na Tolu ada hubungan yang menarik untuk diperhatikan berkaitan kesetaraan so-sial, yaitu hubungan antara Hula-hula dengan Boru. Hubungan ini sering diang-gap sebagai bentuk kesenjangan sosial, sehingga dalam perkembangan zaman banyak orang Batak yang telah memiliki paradigma yang berubah terhadap falsafah Dalihan Na Tolu. Artikel ini mengkaji bahwa hubungan antara Hula-hula dan Boru dalam falsafah Dalihan Na Tolu adalalah sebuah kesetaraan so-sial dan tidak bertentangan dengan iman Kristen. Perspektif iman Kristen akan menjadi penyempurna falsafah Dalihan Na Tolu karena dalam penerapannya telah membangun falsafah tersebut dengan dasar kasih Kristus sebagai mana yang dituliskan Paulus dalam Galatia 3:28. Pemaknaan dari sisi konteks Galatia 3:28 memberikan korelasi yang jelas mengenai kesetaraan dalam falsafah Dalihan Na Tolu. Penelitian ini menggunakan metode kualitatif dan deskriptif.